REALISASI FRASA ATRIBUTIF DALAM WACANA NARASI MAHASISWA UNIVERSITAS BINA DARMA DAN APLIKASINYA DALAM PEMBELAJARAN - Muchti, Andina (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2021)
This research will describe attributive endocentric phrases in the narration text student of Bina Darma University, and the application of Bahasa Indonesia learning, especially material for editing phrases. The method used in this research is a qualitative description method. This data research is in the form of words and phrases. The data source for this research is the narrative story student of Bina Darma University. The data collection technique used was the reading and note taking technique. Data analysis using descriptions. The research results presented in this article as a sample are 5 data. The data is intended to be realized in Indonesian language learning, especially the material of editing phrases. The realization of the results of the analysis of attributive endocentric phrases in learning can be applied in the teaching material for editing phrases. The teacher can use the results of the analysis as teaching material in the learning process which is conveyed in the lesson plan